Effect of a Novel Training Program in Patients With Chronic Shoulder Pain Based on Implicit Motor Learning: Pilot and Feasibility Study. - Annelies Maenhout; Wieger Heijenk; Peter Glashouwer; Lore Quatacker; Luna Praet; Dorien Borms (International Journal of Sports Physical Therapy)
# Background